Geological conditions of coalbed methane accumulation in the Hancheng area, southeastern Ordos Basin, China: Implications for coalbed methane high-yield potential - Chen Guo (Energy Exploration & Exploitation, 2019)
The Hancheng area is a hot spot for coalbed methane exploration and exploitation in China. Structure is a key factor affecting coalbed methane accumulation and production in the Hancheng area. For a better understanding of the coalbed methane accumulation conditions and high-yield potential, this study investigates the structural patterns and evolution, the hydrogeological conditions, and the geothermal field in the coal-bearing strata in the Hancheng area. Then, the spatial distribution of the coalbed methane content and the tectonic deformation of the coal seam are evaluated. Finally, the critical depth for coalbed methane enrichment and a high-yield potential are revealed, and the favorable areas for coalbed methane development are predicted. The following conclusions are obtained: (1) Under the Yanshanian SE–NW trending maximum principle stress, the Hancheng overturned anticline was formed and subsequently subjected to uplift and erosion along its axis, which led to the NW limb of the anticline forming the current uniclinal structure of the Hancheng area; (2) Four degrees of tectonic deformation in the coal seam are identified based on structural curvature analysis. The moderately deformed area shallower than 800 m would benefit coalbed methane production with higher permeability. Most of the locations of coal and gas outburst events that occur during coal mining were distributed along the highly and very highly deformed areas; (3) The gas content gradually increases along the NW-trending inclination of the coal seam. 400 m and 800 m are discriminated as the critical depth levels for controlling coalbed methane accumulation and a high yield. Secondary biogenic methane was generated in the shallow formations; and (4) The Hancheng area is divided into four ranks for determining coalbed methane development potential. From high to low, they are ranked A, B-1, B-2, and C. Most of the high-yield wells are located in the areas ranked A and B-1.